Pengaruh Pengembangan Sumber Daya Manusia Dan Pendidikan Dalam Rangka Meningkatkan Pertumbuhan Ekonomi - Erma Hotnijar Siregar; Winda Khairani Hasibuan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Human resources are the potential contained within humans to realize their role as adaptive and transformative social creatures who are able to manage themselves and all the potential contained in nature towards achieving a prosperous life in a balanced and sustainable order. Competent and high-quality human resources are needed to support productivity and activities so that the country's goals can be achieved perfectly. Human resources are also a key factor in economic reform, namely how to create quality human resources who have high skills and competitiveness in global competition. Education has an important role in the era of information and knowledge, where rapid changes occur in many areas of life. Mind, knowledge, and organization are important factors in the information and knowledge era. Educational institutions must be able to prepare graduate profiles who have competencies that are relevant to the new era or the information era.